Perception of middle school students about a vocational orientation program: a qualitative study - Castellanos, Luis Mario (Universidad Autónoma de Tamaulipas, 2017)
The practices of vocational orientation emerge in industrial capitalist societies of the twentieth century, at the beginning, these were understood as a response to the adaptive demands of these emerging societies. This study aims to describe the perception of middle school students about the vocational orientation provided by a program called "I want to be a Teacher" which is developed by a university in southern Chile. The nature of this study is qualitative, therefore, an intentional sampling of typical cases was used and the sample consisted of 4 high school students who attended the vocational orientation program. Data collection was performed using a semi-structured interview that had 10 initial questions which were deepened according to the research objective, this was complemented with field note, synthesis memo and audio record. The weighted hierarchical content analysis method was used to analyze the results, these indicate that the participants evaluate positively the vocational orientation that the program delivers, and they consider that a fundamental aspect of the program is the psychological and academic orientation. The results are discussed according to the proposed literature and the limitations and future lines of research are indicated.